Montenegro : Technical Assistance Report-Macroprudential Policy Framework. (IMF Staff Country Reports; Country Report ;, 2017)
This Technical Assistance Report discusses technical advice and recommendations given by the IMF mission to the authorities of Montenegro regarding establishment of a macroprudential policy framework. The macroprudential policy mandate should rest with the Central Bank of Montenegro, with enhanced accountability, given its financial stability mandate and systemic risk analytical capacity. The mandate should be explicitly spelled out in a single published document that sets out a policy framework with clear objectives and specific indicators and instruments. Accountability for macroprudential policy decisions should also be strengthened.